PENGUKURAN KINERJA RANTAI PASOK TEMBAKAU PADA BAGIAN HULU DI PR. X MALANG - Febriana, Riska Ayu; Riana, Fitria Dina; Aprilia, Anisa (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Activities in the supply chain have problems related to uncertainty, to be faced in this condition the business actors need to know their performance and improve their performance. The level of best or bad performances of a company has based on the application of supply chain management in managing the business activities. The implementation of supply chain management is faced with a problem such as uncertainty of market conditions about price and quantity of supply and demand that can affect the operational activities of the supply chain. The supply chain problem also occurs in the tobacco supply chain as the plantation commodity with high economic value and the seasonal characteristic. The upstream side of the tobacco supply chain is needed to determine the performance that has been achieved. Therefore, research on the performance measurement of upstream tobacco supply chain at PR. X Malang is important. The purposes of this study are to describe the mechanism of implementation of tobacco supply chain management on the upstream side, and analyzing the performance of the upstream of the tobacco supply chain, and formulate a strategy to improve the upstream of supply chain performance. The analysis used in this study is based on the SCOR model with five core processes (plan, source, make, deliver, return) and five performance attributes (reliability, responsiveness, agility, cost, asset). This study uses 3 key informants consisting of farmers, collectors, and manufacturers with purposive techniques. The result of this study shows that the farmer performance needs an improvement based on the flexibility and TSCC (total supply chain cost) matrix performance, the collector performance needs an improvement based on TSCC performance matrix and manufacture performance needs an improvement based on the flexibility and TSCC matrix performance.